Dukun Bayi dan Kejadian Tetanus Neonatorum: Refleksi Kegagalan Program Kemitraan Bidan dan Dukun - Rokhmah, Dewi; Khoiri, Abu; Falih, Ahmad (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2018)
Background. Tetanus Neonatorum (TN) is one most risk disease caused death. TT status screening program has been implemented by Jember District Health Department in early 2010 as a follow up from frequent cases and deaths of TN (CFR >50%). However, there were 6 cases and 3 deaths of TN after the program because pregnant women still preferred going to the traditional birth attendances than going to the midwives. Objective. The purpose of this study was to analyze the role of witchdoctor in birth process on woman with TN case, described the default of partnership midwife and witchdoctor program. Method. This reseach used qualitative method, by indepth interview to wicthdoctor with TN death case. Support informants are taken from midwife and pregnant woman with TN case. Data were analysed by thematic content analysis. Results. The results showed that all traditional birth attendance used tools and traditional methods unsterilized, they have not had partnership with midwife, they never got training, they did not have knowledge about TN. The failure of midwife and traditional birth attendance partnership program is evident by the numbers of pregnant women went to traditional birth attendance and death cases of TN.